Engaged but Ambivalent: A Study of Young Indigenous Australians and Democratic Citizenship - Walsh, Lucas; Zyngier, David; Fernandes, Venesser; Zhang, Hongzhi (The Australian Journal of Indigenous Education, 2019)
In 2016, data was collected from eighty-one Indigenous young people in Australia through surveys and focus groups, which provide insight into the experiences of citizenship and democracy by young Indigenous Australians. This paper examines the attitudes of these young Indigenous Australians in relation to conventional political, economic and cultural domains of citizenship. Discussion highlights young Indigenous Australians’ perceptions of their spheres of influence, as well as their perceptions of the barriers and enablers to influence their worlds. The findings are used to critically interrogate the concept of democratic citizenship through recent scholarly lenses including the following: affective and spatial dimensions of citizenship; resilience and identity; and daily acts of citizenship. Connection to the local community is important to many of the young Indigenous participants in this study. This sends a powerful message to educational practitioners and policy makers: The local is a key site in positively shaping the democratic citizenship of young people, with an opportunity for schools and educational activities in local settings to play a central role.